CXCR3 chemokine receptor signaling mediates itch in experimental allergic contact dermatitis. Issue 9 (September 2015) - Qu, Lintao; Fu, Kai; Yang, Jennifer; Shimada, Steven G.; LaMotte, Robert H.
Abstract : Abstract: Persistent itch is a common symptom of allergic contact dermatitis (ACD) and represents a significant health burden. The chemokine CXCL10 is predominantly produced by epithelial cells during ACD. Although the chemokine CXCL10 and its receptor CXCR3 are implicated in the pathophysiology of ACD, it is largely unexplored for itch and pain accompanying this disorder. Here, we showed that CXCL10 and CXCR3 mRNA, protein, and signaling activity were upregulated in the dorsal root ganglion after contact hypersensitivity (CHS), a murine model of ACD, induced by squaric acid dibutylester. CXCL10 directly activated a subset of cutaneous dorsal root ganglion neurons innervating the area of CHS through neuronal CXCR3. In behavioral tests, a CXCR3 antagonist attenuated spontaneous itch- but not pain-like behaviors directed to the site of CHS. Injection of CXCL10 into the site of CHS elicited site-directed itch- but not pain-like behaviors, but neither type of CXCL10-evoked behaviors was observed in control mice. These results suggest that CXCL10/CXCR3 signaling mediates allergic itch but not inflammatory pain in the context of skin inflammation. Thus, upregulation of CXCL10/CXCR3 signaling in sensory neurons may contribute to itch associated with ACD. Targeting the CXCL10/CXCR3 signaling might be beneficial for the treatment of allergic itch. Abstract : In a murine model of allergic contact dermatitis, the chemokine CXCL10, acting on the receptor CXCR3, directly activates cutaneous sensory neurons to elicit itch.